Ovarian Torsion: Multimodality Review of Imaging Characteristics. Issue 6 (November 2015) - Smolinski, Sara E.; Kreychman, Alena; Catanzano, Tara
Abstract : Abstract: We present a case of ovarian torsion in pregnancy with demonstration of vascular flow on sequential Doppler ultrasonography. Magnetic resonance imaging demonstrated ovarian enlargement and edema. Mild symptoms and low clinical suspicion, in addition to risks associated with pregnancy prevented early laparoscopic examination, though torsion was considered. Progressive ovarian enlargement supported surgical intervention, which confirmed the presence of torsion. This case report reviews multimodality imaging characteristics of ovarian torsion, re-emphasizing the significance of ovarian morphology.